Evaluating biological alternative material for poultry bedding - Norsuhada, Sudin (2014)
Poultry production is widely dispersed across the globe and one of the important issues for growers is the selection of suitable bedding material. Recently, low supplier of the raw material increases the price of bedding material. This study aimed to evaluate the most suitable biological alternative bedding material for poultry production. The effects of moisture content, pH value and ammonia nitrogen absorption by bedding material are considered. The selected materials were banana fiber, coconut fiber, oil palm frond fiber and rice straw. Ammonia nitrogen concentration of bedding material was determined by using HACH spectrophotometer. Based on result, within these four alternative bedding materials, banana fiber shows the best absorbent bedding material where the rate of ammonia concentration is increase in-every an hour and followed by rice straw. The more concentration of ammonia nitrogen in the bedding material after experiment showed the ability of the material to absorb ammonia nitrogen emission from chicken manure in poultry house. This alternative bedding material has potential to minimize ammonia nitrogen in poultry house since their pH already in acidic condition and moisture content also in the range of published value 30 to 70%. The pH of the sample must in form of acidity in order to maintain ammonia the non-volatile ionized from (ammonium) and significantly can reduce the ammonia nitrogen emission. For further study, this study needs to be conduct in real poultry house to observe and analyze the potential of this alternative bedding material in real environment.